Measuring the comprehensive wage effect of changes in unit labor cost - Hideyuki Mizobuchi (Journal of Economic Structures, 2015)
Unit labor cost (ULC) is defined as labor compensation per value added. It captures the cost competitiveness of industries and countries. As labor compensation is wage multiplied by hours worked or number of people employed, it is easy to show that ULC is wage divided by labor productivity. Thus, changes in ULC are often discussed in the context of wage increases and labor productivity. However, a higher wage induces firms to substitute labor with capital, which affects labor productivity. However, the conventional decomposition of changes in ULC dismisses this indirect impact of wage on ULC through labor productivity. We propose an alternative decomposition of the change in ULC with a measure of a comprehensive wage effect, which fully captures its direct as well as indirect impact. It allows us to understand more accurately the role of wage changes in enhancing cost competitiveness. Furthermore, we compare measures of the wage effect under two decompositions, using data from 18 OECD countries over the 1995 - 2005 period. We find the wage effect to be significantly overestimated under the conventional decomposition. This study looks at ULC for the whole country as well as for two sectors-manufacturing sector and electricity, gas, and water supply sector.
Keywords: C43; D24; O47; E31; 330; Unit labor cost; Malmquist index; Index number; Manufacturing sector; Energy sector